IMPLEMETASI KEBIJAKAN ALOKASI DANA DESA DI DESA SARUDU KECAMATAN SARUDU KABUPATEN MAMUJU UTARA - Arifuddin Arifuddin (Katalogis, 2018)
This study aimed to determine and to analyze the implementation of Village Fund Allocation Policy in Sarudu Village Sarudu District North Mamuju Regency. This study used the theory of Edward III stating 4 indicators of policy implementation, namely Communication, Resources, Disposition, and Bureaucracy. The research method used was qualitative, and the informants of this study were specified purposively deemed to know the problems studied, while the informants were Head of Village Governance Division at North Mamuju Board for Village Community and Governance Empowerment, Head of Sarudu Village, Secretary of Sarudu Village, Speaker of Sarudu Village Consultative Body, and Public Figures of Sarudu Village. The data used were primary and secondary data. Data were collected through observation, interview, and documentation. The results showed that communication is one of the main factors of policy implementation, the socialization intensity of the village fund allocation policy was still lacking. Resources are the main factors that must be held by every institution, no any support facility for Village Fund Allocation Policy in the form of budget from other income of the village, and human resources were revealed that the ability level of the implementers were uneven. Likewise Disposition, it was revealed that not every implementer had a good response to Village Fund Allocation Policy. While, the inhibiting factor was bureaucratic structure wherein no division of tasks between the Project Management Team of Village Fund Allocation and lack of coordination in the Project Management Team in implementing the policy.